All Questions Topic List
Trigonometry Questions
Previous in All Question Next in All Question
Previous in Trigonometry Next in Trigonometry
Question Number 185486 by sonukgindia last updated on 22/Jan/23
Answered by a.lgnaoui last updated on 23/Jan/23
A−(B+C)=0A+B+C=2(B+C)=2AA+B−C=A−(B+C)+2B=2BA−B+C=A−(B+C)+2C=2Csin(A+B+C)+sin(A+B−C)+sin(A−B+C)2sinAcosBcosC=sin2A+sin2B+sin2C2sinAcosBcosC=2[sinAcosA+sinBcosB+sinCcosC]2sinAcosBcosC=cosAcosBcosC+tanBsinAcosC+tanCsinAcosB=cosAcosBcosC+1sinA(tanBcosC+tanCcosB)=cosAcosBcosC+1sinA(sinB+sinCcosBcosC)=1cosBcosC[cosA+sinB+sinCsinA](1)sinA=sin(B+C)(1)=1cosBcosC[(cos(B+C)+sinB+sinCsin(B+C))]=1cosA+sinBsinC[cosA+sinB+sinCsinA]
Commented by mr W last updated on 23/Jan/23
thisislikewhenyoutrytosimplify12to42+31−12.
Answered by Frix last updated on 23/Jan/23
a=b+csin(a+b+c)+sin(a+b−c)+sin(a−b+c)==sin(2b+2c)+sin2b+sin2c2sinacosbcosc==2cos2bsinccosc+2sinbcosbcos2c==sin(2b+2c)+sin2b+sin2c2⇒answeris2
Terms of Service
Privacy Policy
Contact: info@tinkutara.com